The shadow of a year : the 1641 rebellion in Irish history and memory - Gibney, John, 1976- (History of Ireland and the Irish diaspora., 2013)
In October 1641, a rebellion broke out in Ireland. Dispossessed Irish Catholics rose up against British Protestant settlers whom they held responsible for their plight. This uprising, the first significant sectarian rebellion in Irish history, gave rise to a decade of war that would culminate in the brutal re-conquest of Ireland by Oliver Cromwell. It also set in motion one of the most enduring and acrimonious debates in Irish history. Was the 1641 rebellion a justified response to dispossession and repression? Or was it an unprovoked attempt at sectarian genocide? In this book, the author examines three centuries of this debate.